65 Long term clinical outcomes following percutaneous coronary intervention to in-stent restenosis of saphenous venous graft in acute coronary syndrome. (6th June 2022) - Zakai, Maria; Osman, Khalid; Thant, Kyi Zin; Freestone, Bethan; Bhatia, Gurbir; Ment, Jerome; Kumar, Nitin; Lee, Kaeng; Pitt, Michael; Pulikal, George; Athukorala, Sampath; Basavarajaiah, Sandeep
Abstract : Aims: The longevity of saphenous vein graft (SVG) is poor. However, if SVG has already been stented and if there is restenosis within the previously stent then long-term outcomes is considered to be poor, although there is no long-term data on the treatment of SVG restenosis. In this study, we have assessed long-term outcomes following treatment of SVG-restenosis in acute coronary syndrome (ACS). Methods: A retrospective analysis was conducted on all patients who received PCI to a saphenous venous graft in the context of acute coronary syndrome between January 2011 to December 2021. Follow-up was achieved by reviewing admission records and previous clinic visits. The outcomes measured included: cardiac death, target-vessel myocardial-infarction (TVMI), target lesion revascularisation (TLR), target vessel revascularisation (TVR) and MACE (combination of cardiac death, target-vessel MI and target vessel revascularisation). Results: 30 patients with a mean age of 73 (range 56–90 years) were treated with PCI to SVG in context of ACS of which 30% were ST-segment elevation myocardial-infarction (n=9). 80% males (n= 24), 57% were diabetic (of those 71% were insulin dependent), 40% (n=10) had renal-dysfunction (GFR <60 ml/min) and 38% had impaired left ventricular function (ejection-fraction < 50%). Based on the angiographic review, 30% (n=9) of grafts were considered degenerate (ectatic, aneurysmatic and/or thrombotic). During the procedure, the majority (86%) used semi-compliant balloons and 47% non-compliant balloons, thrombus aspiration was used in 17% cases and the use of GPIIB/IIIA inhibitors was 10%. Slow-flow/ no-flow occurred in 27% (n=8) of procedures necessitating use of intra-coronary vasodilator in 10% of cases (n=3) with overall success rate of 96% (n= 29). In 5 cases (16%), drug eluting balloon (DEB) was used, the others (84%) utilised stents (n=25). The average stent diameter was 3.4 mm and length was 25 mm and average DEB diameter was 3.4 mm and length was 31 mm. There were 2 deaths before discharge. During a median follow-up of 1400 days (46 months), cardiac death occurred in 9 patients (30%), target vessel MI was in 10% (n=3); TLR was 17% (n=5), TVR 17% (n=5) and overall MACE rate was 47% (n=14). Conclusions: Our data suggest that the long-term outcomes following intervention to re-stenosis of SVG-PCI in ACS has an unacceptably high MACE rate in this small study group. Given this, maybe we should consider PCI to native circulation if there is such an option especially given the current improvement in complex PCI techniques. Conflict of Interest: None